'Model' versus 'everyday' patients: can randomized controlled trial data really be applied to the clinic?. Issue 3 (March 2017) - Hershkop, Eliyakim; Segal, Linoy; Fainaru, Ofer; Kol, Shahar
Abstract: New drug approval requires a new drug to undergo rigorous clinical trials to determine its efficacy and safety. A drug is approved only for the population on which it was tested, i.e. those who meet the inclusion criteria of the trial. The aim of this study was to determine what percentage of 'real life' patients in our clinic meet the inclusion and exclusion criteria used in large-scale clinical trials required for drug registration in the field of assisted reproduction. All 265 consecutive patients with pertinent data treated in a tertiary centre IVF Unit during 2015 were surveyed. Their demographic and clinical parameters were compared with inclusion and exclusion criteria used in nine major clinical trials. Only 97 out of 265 (37%) patients met the consensus inclusion criteria as defined by the nine clinical trials. The number of oocytes retrieved was 9.10 ± 5.34 in the patients that met the inclusion criteria ( n = 97) versus 6.90 ± 5.23 ( P = 0.00122) in those that did not ( n = 168). Most 'real life' patients who come for treatment at a tertiary IVF centre do not meet the consensus of inclusion and exclusion criteria used for major clinical trials.